PENGARUH PENERAPAN MEDIA E-CROSSWORD PUZZLE TERHADAP PEMAHAMAN SISWA KELAS IV PADA MATERI KONSEP SENI RUPA - Paluvi Andyani Sulaeman; Julia; Diah Gusrayani (EDU RESEARCH, 2024)
This research is motivated by the frequent hindrance of students' understanding of visual arts due to the lack of diverse and engaging interactive learning media. Conventional teaching methods often fail to captivate students into active participation and deep understanding. The use of technology as a learning medium could potentially enhance students' comprehension of visual arts topics. Interactive technological learning media can sustain students' interest in learning and achieve educational goals. Therefore, this study aims to investigate the impact of implementing E-Crossword Puzzle media on fourth-grade students' understanding of visual arts concepts and to compare it with traditional teaching methods. The research employs a quasi-experimental method within a quantitative approach using a Nonequivalent Pretest-Posttest Control Group Design. The study involves two schools and 60 fourth-grade students divided into experimental and control groups for E-Crossword Puzzle and conventional teaching, respectively. The results indicate a positive influence of E-Crossword Puzzle media on learning, with average scores increasing from 44.75 before treatment to 77.08 afterward. In contrast, conventional teaching showed average scores of 56.08 in the pretest and 60.58 in the posttest. Thus, the findings suggest that E-Crossword Puzzle media has a more significant impact compared to traditional teaching methods. E-Crossword Puzzle media can serve as an effective alternative to enhance fourth-grade students' understanding of visual arts concepts and promote active participation in the learning process.